2015
DOI: 10.1038/jhh.2015.81
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of adiposity and cardiorespiratory fitness with resting blood pressure of South African adolescents: the PAHL Study

Abstract: Obesity and low level of cardiorespiratory fitness are associated with high blood pressure in both adolescents and adults. The objective of this study was to assess the relationship of adiposity and cardiorespiratory fitness with resting blood pressure in 14-year-old male and female adolescents. Cross-sectional data on 310 adolescents (31.8% boys) from six high schools, who were participating in the on-going Physical Activity and Health Longitudinal Study, were collected. Height, weight, body mass index (BMI),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
26
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 66 publications
6
26
1
Order By: Relevance
“…The article presents findings from cross-sectional (2011) data from PAHLS. Detailed information about the participants, method of data collection and sample size has been published elsewhere [35,38]. The sample comprised 238 adolescents (90 boys and 148 girls) with an average age of 14.9 ± 0.8 years.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The article presents findings from cross-sectional (2011) data from PAHLS. Detailed information about the participants, method of data collection and sample size has been published elsewhere [35,38]. The sample comprised 238 adolescents (90 boys and 148 girls) with an average age of 14.9 ± 0.8 years.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous publications on the sample under study in the Physical Activity Health Longitudinal Study (PAHLS) reported findings on body composition, physical fitness, lipid profiles, blood pressure, physical activity and the social correlates of physical activity [34,35,36,37,38], but none of these studies have investigated participation in organized sports (i.e., as a component of PA and not competitive sport) in relation to body composition, physical fitness and PA social correlates. In general, when studying youth PA, the influence of different factors must be considered (i.e., age, gender, type of support, weight status, type of sport and socio-economic status).…”
Section: Introductionmentioning
confidence: 99%
“…[56,57] Higher adiposity has been associated with poor blood pressure and cardiovascular fitness measures. [59] Since the high prevalence of overweight/obesity persists, the grade remains a D. Undernutrition C Based on regional studies, undernutrition remains a problem in both rural and urban areas. [56,[60][61][62] No recent national data on indicators of undernutrition (stunting, wasting, underweight) are available for the 5 -15-yearold age group.…”
Section: Articlementioning
confidence: 99%
“…9 Bearing in mind the importance of epidemiological studies in hypertension, this special issue of the Journal of Human Hypertension has been devoted entirely to epidemiological studies. We have papers from China, 10,11 Guinea, 12 Bangladesh, 13 Iran, 14 Canada, 15 South Africa 16 and Nigeria. 17 Interestingly, there are still new data being published from populations that have previously not been studied.…”
mentioning
confidence: 99%
“…Studying disease patterns in small ethnic groups, such as the indigenous population in Canada, 15 or specific age groups, such as adolescents in South Africa, 16 also gives us important information showing that each ethnic group or each age group is unique and has to be dealt with differently.…”
mentioning
confidence: 99%